Migrants remittances and fertility in the Post-Soviet states - Ibrokhimov, Boburmirzo; Javed, Rashid; Mughal, Mazhar (Post-communist economies, 2023)
The demographic consequences of remittance flows to the developing countries have so far received scant attention. In this study, we examine the impact of migrants' remittances on fertility by employing unbalanced panel data from Post-Soviet states. During the last three decades, these countries witnessed large-scale out-migration accompanied by high inflows of migrants' remittances, and went from a high mortality - high birth rate to a low mortality - low birth rate regime. Employing standard panel estimation methods and instrumental variable (IV) approach, we find evidence for a significant negative association between remittances and fertility. These findings are robust to alternate measures and strategies. The impact of remittances is significant beyond a minimum threshold and has strengthened over time. The findings of the study highlight the remittances' substitution effect contributing to the post-communist countries' demographic transition.